Sustainably Intensified Production Systems Impact on Nutrition (SIPSIN) Round 1, Ethiopia - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
The project aims to evaluate the implications of sustainable intensification of crop and livestock production systems (SIPS) on human nutrition in northern Ethiopia. The existing infrastructure and ongoing research and development of the Innovation Lab for Small Scale Irrigation (ILSSI) in the Lake Tana basin of Northern Ethiopia is used as a platform to efficiently conduct research to evaluate SIPS for crop and livestock production and their environmental, economic and nutritional consequences.